Identification of Leading Fishing Commodities in Situbondo - Endang Suhesti (Journal of Aquaculture Science, 2021)
The waters in the Province of West Nusa Tenggara (NTB) are a very potential area for the development of the capture fisheries sector because these waters are fish migration areas. The high potential of fish resources in Situbondo Regency must be utilized optimally so as to provide benefits for the fishing community. The strategy to utilize fish resources is to determine the superior commodity. The basic method used is a descriptive method by taking the research area purposively. Through field observations, interviews, and institutional surveys, supporting data were obtained which were analyzed using the LQ (Location Quotient) analysis method. The type of data used is capture fisheries sector production data from 2018 to 2020. The priority agricultural commodities that are prioritized to be developed in each sub-district in Situbondo District are squid in Banyuglugur District, scad fish in Besuki and Suboh Districts, catfish in Mlandingan District and Asembagus, selar fish in Bungatan District, shrimp in Kendit District, stingray in Panarukan District, lemuru in Mangaran District, petek fish in Banyuputih District, crabs in Kapongan and Arjasa Districts. The leading and most produced commodities in Situbondo Regency are grouper, mackerel, and crab.Keywords: fishing; Main commodity of Situbondo Regency